Automation link checker testing with continuous integration - Erik Carla Wijaya, Joe; Suganda Girsang, Abba (International Journal of Engineering and Technology, 2018)
Many links from websites are damaged due to the development of an increasingly large and complex website features. To ensure that no links are broken there is a need for a link checker testing application. But manual testing requires a lot of resources, expensive cost, and takes a long time to check the whole deployment must be done every day, so in this study the manufacture of link checker testing application will run automatically and integrated with Jenkins. With this application, developers can fix broken links in the development stage before being consumed by the public. Automation link checker testing application is using Jenkins as continuous integration tools, Shell Script, PHP Unit framework and PHP programming language will check all the links in the website automatically and report from the test results. Once compared with manual link checking, the test automation application of this link checker is more accurate and faster than checking links manually.